2015
DOI: 10.3390/ijerph120911528
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adiponectin and Leptin Concentrations in Relation to Body Fat Distribution, Hematological Indices and Lipid Profile in Humans

Abstract: The purpose of the study was to evaluate the relationship between serum adiponectin and leptin concentrations and body composition, hematological indices and lipid profile parameters in adults. The study involved 95 volunteers (BMI from 23.3 to 53 kg/m2). Anthropometric parameters were measured: body weight and height, waist and hip circumference, waist-to-hip ratio, body fat mass (BMF), subcutaneous and visceral fat mass (SFM, VFM), lean body mass (LBM), skeletal muscle mass (SMM). In serum we determined adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 67 publications
(96 reference statements)
6
30
2
1
Order By: Relevance
“…Physical activity increases plasma adiponectin concentrations in humans, and there is a negative association between adiponectin and BMI as well as body fat . Our results demonstrate a correlation between changes in adiponectin and BFP (Figure A), suggesting that participants with greater increases in adiponectin had larger decreases in BFP.…”
Section: Discussionmentioning
confidence: 52%
“…Physical activity increases plasma adiponectin concentrations in humans, and there is a negative association between adiponectin and BMI as well as body fat . Our results demonstrate a correlation between changes in adiponectin and BFP (Figure A), suggesting that participants with greater increases in adiponectin had larger decreases in BFP.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, L/A ratio was higher and correlated with weight and FM in patients. In the literature, adiponectin is negatively correlated with insulin resistance and obesity' parameters like BMI (Maeda et al, 2002;Spranger et al, 2003;Weiss et al, 2004), body weight as well as with lean body mass and the lipid indicators LDL-chol and triglycerides (Lubkowska et al, 2015). In ASD patients, significant lower levels of adiponectin were observed when compared to healthy controls, suggesting a role of adiponectin in this pathology (Fujita-Shimizu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas leptin is recognized as a proinflammatory cytokine, adiponectin downregulates the expression and release of many proinflammatory immune mediators (López-Jaramillo et al, 2014). Considering that adiponectin was negatively correlated with body weight (Lubkowska et al, 2015) and leptin was associated with FM (Dalskov et al, 2015), one can suppose that our data regarding the positive correlations of L/A ratio with weight and FM in patients could be related much more to higher leptin levels than to the L/A ratio, since adiponectin levels were similar between groups. In addition, there was no inverse correlation between leptin and adiponectin in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluating the relationship between leptin and thyroid hormones in humans with chronic renal failure and transplanted patients showed no correlation of leptin with hemoglobin (MALYSZKO et al, 2006). Conversely, Lubkowska et al (2015) observed negative relationship between leptin doses in the blood and red blood cells, hemoglobin and hematocrit. The negative relation between leptin and corpuscular hemoglobin concentration in this study suggests a possible effect of hypoxia on leptin concentration in female dogs.…”
Section: Discussionmentioning
confidence: 96%
“…Most of the research on leptin and adiponectin effects on the cardiovascular and respiratory system has been conducted on obese and/or diabetic rats and humans (LUBKOWSKA et al, 2015;SENADOR et al, 2009;SIKKA et al, 2010). Moreover, there are few reports of these effects on haematological parameters in domestics animals.…”
Section: Introductionmentioning
confidence: 99%